2019
DOI: 10.1177/0272431619870604
|View full text |Cite
|
Sign up to set email alerts
|

Attachment as Moderator of Perceived Social-Class Discrimination on Behavioral Outcomes Among Chinese Migrant Children

Abstract: In this study, we examined the relations between perceived social-class discrimination, attachment, and behavior problems in a sample of Chinese migrant children in Beijing (age [Formula: see text] = 11.48, SD = 1.12; n = 179). Data were collected from two migrant schools in Beijing. The participants completed measures of perceived social-class discrimination, attachment to parents and peers, and internalizing and externalizing behavior problems. The results indicated that perceived social-class discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Although associations between perceived discrimination due to socioeconomic disadvantage and psychological distress have been found in previous studies (Gamarel et al, 2012;Song et al, 2020), the specific contributions of aspects of selfcompassion (CS, RUS, or overall SC) in its buffering effect on this association have not been examined. It is especially useful to investigate these effects with a longitudinal design, as findings from cross-sectional research are somewhat limited regarding the directionality of the effects and predictability of the associations between variables (Chan et al, 2020;Sick et al, 2020).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Although associations between perceived discrimination due to socioeconomic disadvantage and psychological distress have been found in previous studies (Gamarel et al, 2012;Song et al, 2020), the specific contributions of aspects of selfcompassion (CS, RUS, or overall SC) in its buffering effect on this association have not been examined. It is especially useful to investigate these effects with a longitudinal design, as findings from cross-sectional research are somewhat limited regarding the directionality of the effects and predictability of the associations between variables (Chan et al, 2020;Sick et al, 2020).…”
mentioning
confidence: 91%
“…Perceived discrimination due to socioeconomic disadvantage (also called socioeconomic discrimination, socioeconomic status/position discrimination, perceived social class discrimination) has been investigated among various groups of people (e.g., African Americans, Chinese migrant children) in recent years (Haeny et al, 2019;Song et al, 2020). Perceived discrimination refers to a perception in interacting with others of stigmatization and unfair treatment (e.g., relatively deficient education resources) related to one's own devalued or threatened social identity (Link & Phelan, 2001;Schmitt et al, 2014).…”
mentioning
confidence: 99%
“…These students are likely to have less access to useful resources (e.g., adequate financial support) to facilitate their academic achievement before graduating ( 8 ) and are more likely to experience unfair treatment (e.g., a lack of fair employment opportunities) and relatively poor life situations ( 9 ). Studies have found that perceived social class discrimination is associated with symptoms of depression and anxiety among college students from socioeconomically disadvantaged families ( 10 , 11 ). The response styles theory indicates that paying repetitive and passive concern to the causes and results of stress events and situations may lead to psychological symptoms ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that over 50% of migrant adolescents experienced interpersonal conflicts related to peer aggression (Qin et al, 2008 ). Research has linked the high prevalence rate to discrimination experienced by these children in the receiving places (Lan et al, 2020 ; Song et al, 2020 ). They argued that discrimination impedes the development of these children by increasing their involvement in antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical underpinnings of the GST are supported by empirical research showing a positive relationship between discrimination and adolescent aggression. This relationship has emerged across different adolescent demographic groups including Latinx adolescents (Smokowski and Bacallao, 2006 ; Wright and Wachs, 2019 ), African American youth (Mulvey et al, 2020 ; Xie et al, 2020 ), and Chinese migrant adolescents (Beiser et al, 2010 ; Lan et al, 2020 ; Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%